(untitled) (Brazilian Journal of Health Research, 2021)
Introduction: Neoplasms of the oral cavity are a public health issue, whose main risk factors comprise concomitant cigarette smoking and alcohol intake. Objective: Featuring death cases associated with neoplasias of the oral cavity in the population living in Espírito Santo State, from 2011 to 2016. Methods: Data were collected in the Mortality Information System by taking into account the following variables: municipality of residence, year of death, age group, sex, race, schooling, marital status and place of death. Results: In total, 548 deaths associated with neoplasias of the oral cavity were recorded throughout the investigated period, 77% of cases were men, 49.4% of them were white, 30.5% were in the age group 50-59 years, and 37.8% were married. Moreover, 48.2% of records about schooling was neglected, and the main place of death was the hospital environment (79.6%). The metropolitan health region comprised 60.6% of cases; CID-10 categories C02 (malignant neoplasm of other parts and non-specified parts of the tongue) and C06 (malignant neoplasm of other parts and non-specified parts of the mouth) were the most affected ones - they were followed by C01 (malignant neoplasm of the base of the tongue). Conclusion: It is necessary expanding and providing the population with access to basic oral health care to enable early diagnosis, better treatment and identification of lesions, mainly in populations presenting similar features to those observed in the current study.